Amplification of hot electron flow by the surface plasmon effect on metal–insulator–metal nanodiodes. (9th October 2015) - Lee, Changhwan; Nedrygailov, Ievgen I; Keun Lee, Young; Ahn, Changui; Lee, Hyosun; Jeon, Seokwoo; Young Park, Jeong
Abstract: Au–TiO2 –Ti nanodiodes with a metal–insulator–metal structure were used to probe hot electron flows generated upon photon absorption. Hot electrons, generated when light is absorbed in the Au electrode of the nanodiode, can travel across the TiO2, leading to a photocurrent. Here, we demonstrate amplification of the hot electron flow by (1) localized surface plasmon resonance on plasmonic nanostructures fabricated by annealing the Au–TiO2 –Ti nanodiodes, and (2) reducing the thickness of the TiO2 . We show a correlation between changes in the morphology of the Au electrodes caused by annealing and amplification of the photocurrent. Based on the exponential dependence of the photocurrent on TiO2 thickness, the transport mechanism for the hot electrons across the nanodiodes is proposed.